An Idiom for India: Hindustani and the Limits of the Language Concept. Issue 1 (2nd January 2016) - Lahiri, Madhumita
Abstract : This essay explores the cultural legacy of Hindustani, which names the intimate overlap between two South Asian languages, Hindi and Urdu. Hindi and Urdu have distinct religious identities, national associations and scripts, yet they are nearly identical in syntax, diverging to some extent in their vocabulary. Hindi and Urdu speakers, consequently, understand each other most of the time, but not all of the time, though they can never read each other's texts. Their shared space, Hindustani, finds no official recognition in India or in Pakistan, but it denotes, particularly in the early twentieth century, an aspiration for Hindu–Muslim unity: the dream of a shared, syncretic culture, crafted from the speech genres of everyday life. Beginning with the colonial project of Hindustani, the essay focuses on a discussion of the works of early twentieth-century writers like Nehru, Premchand and Sa'adat Hasan Manto. I argue that the aesthetic project of Hindustani attempted to produce, not a common language, but a common idiom: a set of shared conventions, phrases and forms of address, which would be legible to Indians from all religions and all regions. By theorizing Hindustani as an idiom, and not a language, I explain its persistence in Bollywood cinema well after its abandonment in all literary and official registers. Bollywood, I argue, is Hindustani cinema, not only because of its use of a mixed Hindi–Urdu language in its dialogues, but also because of its development of a set of clearly recognizable, easily repeatable conventions that can surmount linguistic differences.